MOTIVASI GLOBAL FUND MEMBANTU INDONESIA DALAM MENANGGULANGI PERSEBARAN PENYAKIT TUBERKULOSIS - Candra, Gina Putri; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Globalization marked the entrance of the health security issues that become a common threat. Global health security underlies the current framework for global preparedness and response to emerging infectious diseases. One of the infectious diseases that became the world's anxiety is tuberculosis. Therefore, as an international organization, The Global Fund helps by providing grant aid which then allocated for the implementation of tuberculosis prevention program in Indonesia. This study was created to explain the Global Fund motivation to help Indonesia in overcoming the spread of tuberculosis.This study sources was obtained by reviewing the literature either from books, journals, theses, reports, written interview and internet. In this paper, the authors use a globalist perspective with the theory of international organizations. The author uses the level of analysis of individual groups as actors in international relations. This study uses qualitative research methods explanative.In the writting it’s found that the Global Fund helped Indonesia in overcoming the spread of tuberculosis because Indonesia is included in the category of low midle income country and country with a large number of tuberculosis sufferers. Besides that, Global Fund helps Indonesia since it is an implementation of the Kyushu-Okinawa G8 Summit 2000, the UN General Assembly: Declaration of Commitment on HIV / AIDS in June 2001, and the 27th G8 Summit 2001 in Genoa.Keywords: Globalization, Health Security, Global Fund, Indonesia, Tuberculosis